Pressure-jump NMR Study of Dissociation and Association of Amyloid Protofibrils - Kamatari, Yuji O.; Yokoyama, Shigeyuki; Tachibana, Hideki; Akasaka, Kazuyuki (Journal of molecular biology, 2005)
The dissociation and reassociation processes of amyloid protofibrils initiated by pressure-jump have been monitored with real-time 1H NMR spectroscopy using an intrinsically denatured disulfide-deficient variant of hen lysozyme. Upon pressure-jump up to 2 kbar, the matured protofibrils grown over several months become fully dissociated into monomers within a few days. Upon pressure-jump down to 30 bar, the dissociated monomers immediately start reassociating. The association and dissociation cycle can be repeated reproducibly by alternating pressure, establishing a notion that the protofibril formation is simply a slow kinetic process toward thermodynamic equilibrium. The outstanding simplicity and effectiveness of pressure in controlling the protofibril formation opens a new route for investigating mechanisms of amyloid fibril-forming reactions. The noted variation in the pressure-induced dissociation rate with the progress of the association reaction suggests multiple mechanisms for the elongation of the protofibril. The disulfide-deficient hen lysozyme offers a particularly simple model system for thermodynamic and kinetic studies of protofibril formation as well as for screening drugs for amyloidosis.